2021
DOI: 10.1002/adhm.202101679
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling and Experimental Characterization of Extrusion Printing into Suspension Baths

Abstract: The extrusion printing of inks into suspension baths is an exciting tool, as it allows the printing of diverse and soft hydrogel inks into 3D space without the need for layer-by-layer fabrication. However, this printing process is complex and there have been limited studies to experimentally and computationally characterize the process. In this work, hydrogel inks (i.e., gelatin methacrylamide (GelMA)), suspension baths (i.e., agarose, Carbopol), and the printing process are examined via rheological, computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 71 publications
(130 reference statements)
0
23
1
Order By: Relevance
“…[11] For highfidelity printing, solid-to-liquid transitions need to be smooth, spatially localized, rapid, and reversible. [12,13,14] Pioneering studies have demonstrated that jammed microgel assemblies (i.e., granular gels) fulfill these requirements and exhibit excellent rheological properties as supports for embedded printing of delicate structures from soft hydrogels and cells. [15,16] Since then, embedded printing has evolved into a versatile biofabrication platform used for the manufacturing of anatomically accurate tissue components, [17,18,19], [20] patterning of cellular spheroids, [21], [22] engineering of perfusable channels, [23,24,25] and investigation of cellgenerated forces.…”
Section: Introductionmentioning
confidence: 99%
“…[11] For highfidelity printing, solid-to-liquid transitions need to be smooth, spatially localized, rapid, and reversible. [12,13,14] Pioneering studies have demonstrated that jammed microgel assemblies (i.e., granular gels) fulfill these requirements and exhibit excellent rheological properties as supports for embedded printing of delicate structures from soft hydrogels and cells. [15,16] Since then, embedded printing has evolved into a versatile biofabrication platform used for the manufacturing of anatomically accurate tissue components, [17,18,19], [20] patterning of cellular spheroids, [21], [22] engineering of perfusable channels, [23,24,25] and investigation of cellgenerated forces.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with the pinching experienced at low viscosity ratios, this high aspect ratio represents a separate mechanism, where the filament curls over on itself near the nozzle (Figure S7). These curling instabilities were documented in simulations of Newtonian inks and supports at high viscosity ratios, and they were more extensively explored via simulations and experiments in ref .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Next, the melted agarose solution was placed on a magnetic stirrer at 700rpm for 3 hours while cooling to ambient room temperature. This method gives rise to a suspension of agarose particles as the polymer cools under shearing 16,17,19 . To create spherical particles, a batch emulsion method was used.…”
Section: Bioink and Support Hydrogel Fabricationmentioning
confidence: 99%
“…For example, a wide variety of manufacturing methods are used to create microparticles for granular hydrogels, which can result in significant differences in their rheological behaviour, along with the morphology of the particles themselves [16][17][18] . It has been demonstrated that increases in support hydrogel viscosity can improve print resolution, measured by quantifying the width of extruded filaments 9,14,19 . Similarly, lower viscosity in granular support hydrogels has been shown cause greater filament instability and buckling during deposition, particularly when the extrusion and nozzle translation speeds are not matched 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation